Zyciorysy historyczne, literackie i legendarne. Seria 3 - Stefanowska, Zofia; Tazbir, Janusz (Warszawa : Wydawnictwo naukowe PWN, 1992)
Biographical sketchhes of Polish historical, literary and legendary persons.
Wladyslaw Lokietek / Henryk Samsonowicz -- Zawisza Czarny / Franciszek Ziejka -- Zygmunt August / Marceli Kosman -- Mazepa / Julian Maslanka -- Maria Kazimiera Sobieska / Michal Komaszynski -- Tadeusz Rejtan / Roman Kaleta -- Piotr Wysocki / Szczepan Gassowski -- Wincenty Witos / Andrzej Zakrzewski.
Comporte des references bibliographiques et un index.
Keywords: Poland -- Biography